No ways tired : the journey for professionals of color in student affairs. volume III ; - Burke, Monica Galloway; Robinson, U. Monique (Research, advocacy, collaboration, and empowerment mentoring series., 2019)
Even though diversity is currently conveyed as a ubiquitous principle within institutions of higher education, professionals of color still face issues such as discrimination, the glass ceiling, lack of mentoring, and limited access to career networks. Unfortunately, an open channel does not exist for professionals of color to express their frustrations and genuine concerns.The narratives in No Ways Tired present a powerful voice about the experiences of student affairs professionals of color in higher education, including intersecting identities such as race, class, and gender. Furthermore, the narratives are nuggets of personal truth that can serve as a lens for professionals of color who wish to develop strategies to succeed as they traverse their careers in higher education. Through the sharing of their visions of success, lessons learned, and cautionary tales, the authors openly offer insights about how they have created a way to survive and thrive within higher education in spite of challenges and distractions.They also articulate a vision where student affairs professionals of color can develop fully, be authentic, use their agency, and effectively contribute. This book includes recommendations for professionals of color at all levels within higher education and ways to construct opportunities to flourish. The ultimate goal for this book is to promote discussions regarding how professionals of color can be more proactive in developing strategies that are conducive to their professional and personal success as they navigate their higher education careers.